Ideology, Ritual Performance and Its Manifestations in the Rock Art of Timor-Leste and Kisar Island, Island Southeast Asia. Issue 2 (4th December 2017) - O'Connor, Sue; Mahirta,; Tanudirjo, Daud; Ririmasse, Marlon; Husni, Muhammad; Kealy, Shimona; Hawkins, Stuart; Alifah,
Abstract : Painted rock art occurs throughout the islands of the Western Pacific and has previously been argued to have motif and design elements in common, indicating that it was created within the context of a shared symbolic system. Here we report five new painted rock-art sites from Kisar Island in eastern Indonesia and investigate the commonalities between this art and the painted art corpus in Timor-Leste, the independent nation that forms the eastern part of the neighbouring island of Timor. We examine the motifs in the Kisar art and suggest that, rather than being Neolithic in age, some of the figurative motifs more likely have a Metal Age origin, which in this region places them within the last 2500 years.